Time Driven Activity Based Costing dan Implementasinya Pada Jasa Perawatan Kesehatan - azmi, zul (Akuntansi & Ekonomika, 2018)
The determination of value in health care is identified as an outcome per unit of cost that depends on the accuracy of cost measurement. This study aims to review the implementation of Time driven activity based costing (TDABC) in various business areas and use TDABC to determine the cost of health care services in primary clinics. Case study method was conducted at Pratama Clinic. Interviews, direct observation and documentation were conducted to collect data. Results show that TDABC can be used in clinics to measure costs through care pathways. TDABC can help improve effectiveness, reduce costs and inform managers to take decisions to control cost efficiency and evaluate unused capacity. Keywords: Time Driven,  Activity Based Costing, Health Care JEL: M41,I14